2001
DOI: 10.1385/abab:90:2:155
|View full text |Cite
|
Sign up to set email alerts
|

Thermozymes and Their Applications: A Review of Recent Literature and Patents

Abstract: Enzymes from thermophilic microorganisms, thermozymes, have unique characteristics such as temperature, chemical, and pH stability. They can be used in several industrial processes, in which they replace mesophilic enzymes or chemicals. Thermozymes are often used when the enzymatic process is compatible with existing (high-temperature) process conditions. The main advantages of performing processes at higher temperatures are reduced risk of microbial contamination, lower viscosity, improved transfer rates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(114 citation statements)
references
References 69 publications
2
108
0
4
Order By: Relevance
“…Moreover, it has long been recognized that thermophiles represent a source of novel thermostable enzymes (4). Previous study conducted in our laboratory showed the crude proteins from a thermoresistant fungus Aspergillus niger SCTCC 400264 retained high xylanolytic activity after heat treatment, however, there was little information about the genes encoded the xylanases from the strain.…”
Section: Hyperexpression Of Two Aspergillus Niger Xylanase Genementioning
confidence: 94%
“…Moreover, it has long been recognized that thermophiles represent a source of novel thermostable enzymes (4). Previous study conducted in our laboratory showed the crude proteins from a thermoresistant fungus Aspergillus niger SCTCC 400264 retained high xylanolytic activity after heat treatment, however, there was little information about the genes encoded the xylanases from the strain.…”
Section: Hyperexpression Of Two Aspergillus Niger Xylanase Genementioning
confidence: 94%
“…Indeed, carbohydrate conversions are typically performed at elevated temperatures (60 °C or higher), mainly to avoid microbial contamination [20][21][22]. Here, we describe the production of CLEAs of the SPase from B. adolescentis that display exceptional thermal and operational stability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has long been recognized that thermophiles represent a source of novel thermostable enzymes (Bruins et al, 2001).…”
Section: Introductionmentioning
confidence: 99%